Evolutionary Theories and Men's Preferences for Women's Waist-to-Hip Ratio: Which Hypotheses Remain? A Systematic Review - Bovet, Jeanne (Frontiers in Psychology, 2019)
Over the last 25 years, a large amount of research has been dedicated to identifying men’s preferences for women’s physical features, and the evolutionary benefits associated with such preferences. Today, this area of research generates substantial controversy and criticism. I argue that part of the crisis is due to inaccuracies in the evolutionary hypotheses used in the field. For this review, I focus on the extensive literature regarding men’s adaptive preferences for women’s waist-to-hip ratio (WHR), which has become a classic example of the just-so storytelling contributing to the general mistrust toward evolutionary explanations of human behaviour. The issues in this literature originate in the vagueness and incompleteness of the theorizing of the evolutionary mechanisms leading to mate preferences. Authors seem to have rushed into testing and debating the effects of WHR on women’s attractiveness under various conditions and using different stimuli, without first establishing (a) clear definitions of the central evolution concepts (e.g., female mate value is often reduced to an imprecise concept of “health-and-fertility”), and (b) a complete overview of the distinct evolutionary paths potentially at work (e.g., focusing on fecundability while omitting descendants’ quality). Unsound theoretical foundations will lead to imprecise predictions which cannot properly be tested, thus ultimately resulting in the premature rejection of an evolutionary explanation to human mate preferences. This paper provides the first comprehensive review of the existing hypotheses on why men’s preferences for a certain WHR in women might be adaptive, as well as an analysis of the theoretical credibility of these hypotheses. By dissecting the evolutionary reasoning behind each hypothesis, I show which hypotheses are plausible and which are unfit to account for men’s preferences for female WHR. Moreover, the most cited hypotheses (e.g., WHR as a cue of health or fecundity) are found to not necessarily be the ones with the strongest theoretical support, and some promising hypotheses (e.g., WHR as a cue of parity or current pregnancy) have seemingly been mostly overlooked. Finally, I suggest some directions for future studies on human mate choice, to move this evolutionary psychology literature toward a stronger theoretical foundation.